VARIATIONS IN ENVIRONMENTAL CONDITIONS OF INTRACONTINENTAL ASIA OVER THE PAST 1 MA IN HIGH-RESOLUTION GEOCHEMICAL RECORDS FROM BOTTOM SEDIMENTS OF LAKE KHUBSUGUL (MONGOLIA) - Phedorin M.A.; Fedotov A.P.; Saeva O.P.; Bobrov V.A. (My University, 2007)
Progress in the study of planetary changes in the environment and climate based on oceanic and glacial records of the Pleistocene provided the basis for further detailed elaboration of spatiotemporal relationships in climate-forming processes. A particular role in this field belongs to continents. In addition to terrestrial sections, bottom sediments of large continental basins provide no less important information about continental variations in the environment. The Asian intracontinental region comprises the two largest freshwater lakes (Baikal and Khubsugul) with different hydrochemical, biological, and hydrological balances. Previous investigations of geochemical records from Baikal sections established that the observed variations were mainly determined by the climatic factor and changes in the biological and hydrological balance of the lake. In contrast to Baikal, Khubsugul is a mountain lake (1645 m above sea level) and has much smaller dimensions (136 km long, 39 km wide). Therefore, this lake responds more dramatically to variations in the environment, climate, and, particularly, the humidity regime.